Treatment of allergic rhinitis during and outside the pollen season using mobile technology. A MASK study. Issue 1 (9th December 2020) - Bédard, A.; Basagaña, X.; Anto, J. M.; Garcia‐Aymerich, J.; Devillier, P.; Arnavielhe, S.; Bedbrook, A.; Onorato, G. L.; Czarlewski, W.; Murray, R.; Almeida, R.; Fonseca, J. A.; et al.
Abstract: Background: The analysis of mobile health (mHealth) data has generated innovative insights into improving allergic rhinitis control, but additive information is needed. A cross‐sectional real‐world observational study was undertaken in 17 European countries during and outside the estimated pollen season. The aim was to collect novel information including the phenotypic characteristics of the users. Methods: The Allergy Diary – MASK ‐ air –mobile phone app, freely available via Google Play and App, was used to collect the data of daily visual analogue scales (VASs) for overall allergic symptoms and medication use. Fluticasone Furoate (FF), Mometasone Furoate (MF), Azelastine Fluticasone Proprionate combination (MPAzeFlu) and eight oral H1‐antihistamines were studied. Phenotypic characteristics were recorded at entry. The ARIA severity score was derived from entry data. This was an a priori planned analysis. Results: 9037 users filled in 70, 286 days of VAS in 2016, 2017 and 2018. The ARIA severity score was lower outside than during the pollen season. Severity was similar for all treatment groups during the pollen season, and lower in the MPAzeFlu group outside the pollen season. Days with MPAzeFlu had lower VAS levels and a higher frequency of monotherapy than the other treatments during the season. Outside the season, days with MPAzeFlu also had a higher frequency of monotherapy. The number of reported days was significantly higher with MPAzeFlu during and outside the season than with MF, FF or oral H1‐antihistamines. Conclusions: This study shows that the overall efficacy of treatments is similar during and outside the pollen season and indicates that medications are similarly effective during the year.